PENGARUH METODE CERAMAH DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN HAM DI KELAS VII MTS MIFTAHUL MUBTADI’IN KAJJAN BLEGA BANGKALAN TAHUN PELAJARAN 2018-2019 - Moh. Yusuf; Soubar Isman; Ernawati (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
The use and selection of learning methods is an important role in the teaching and learning process. The teacher plays a major role in determining the content and steps in delivering material to students. Things that underlie this research include the lack of interest in learning human rights material and the lack of motivation for students to improve learning outcomes. This study aims to determine the effect of the lecture method in improving student learning outcomes in human rights subjects. This research uses quantitative methods. Quantitative method is a research method in the form of numbers because it uses mathematical symbols related to variables, as well as correlation and direct observation with research objects. This method emphasizes objective phenomena, the design of this study uses numbers, statistical processing, structure and controlled experiments. The results of this study are lecture methods in improving student learning outcomes in human rights subjects in class VIII at MTs Miftahul Mubtadiin Kajjan Blega Bangkalan that there is an influence. This is proven based on data analysis performed using the product moment formula with the calculated value obtained from the correlation coefficient (r) of 1.97 greater than r work, both at the level of 1% sigification with a value of 0.344 or at 5% significance with value of 0.442. The effect is classified as very strong or very high, this is based on "r" with a value of 1.97 which is located above the number 1.00 which the interpretation is very strong or very high. Thus, the research hypothesis (Ha) proposed can be accepted meaning that there is an effect of the lecture method in improving student learning outcomes in human rights subjects in class VIII at MTs Miftahul Mubtadiin Kajjan Blega Bangkalan 2018-2019 academic year.